Correlational indicators of psychosocial adjustment among senior secondary school students in Ogun State, Nigeria (2017)
This study examined correlational indicators of psychosocial adjustment among senior secondary school students in Ogun State, Nigeria. The study adopted the correlational research design. A sample of 700 students' was randomly selected. Reliable instrument was used to elicit the data. The data was analysed using Pearson product moment correlation and multiple linear regression analysis. The result revealed that the independent variables significantly correlated with students" psychosocial adjustment. There was a significant joint contribution of the independent variables (sense of coherence, optimism and self-efficacy) to the prediction of psychosocial adjustment. This suggested that the three independent variables combined accounted for 30.4% (Adj.R2= .304) variation in the prediction of psychosocial adjustment. The most potent factor was optimism, followed by self-efficacy. Sense of coherence was not a potent predictor of psychosocial adjustment. This implies that an increased influence of optimism and self-efficacy increases the likelihood of students' psychosocial adjustment. Among others, it was recommended that school counsellors should design programmes that will help students develop adequate psychosocial adjustment skill to cope with the demands of life. School administrators are also enjoined to organize programmes that emphasise the development of self-efficacy, optimism and sense of coherence in students. Keywords: Psychosocial adjustment, Sense of coherence, Optimism, Self-efficacy, adolescent students.